INNOVATIVE GOVERNANCE: A STUDY ON DTKS MANAGEMENT THROUGH SIKS-NG IN FULFILLING SOCIAL WELFARE IN BOGOR - Mulyana, Ana; Maruapey, Muhamad Husein; Rahmawati, Rita (Administratie: Jurnal Administrasi Publik, 2024)
This study aims to explore innovations in the governance of integrated social welfare data management through the SIKS-NG application and its impact on the fulfillment of social welfare services in Bogor Regency. SIKS-NG is a digital platform that integrates social welfare data from various sources to support the planning and implementation of more effective and efficient social programs. The methodology of this research involves qualitative analysis using secondary data from, interviews with stakeholders, observations, documentation, literacy studies and surveys of beneficiaries. The results of the study show that innovative governance in the management of DTKS through the SIKS-NG application in the context of fulfilling social welfare in Bogor district has been running well. The management of DTKS through SIKS-NG is based on Rogers' innovation attribute that there are innovation characteristics in the system, and the SISKS-NG application provides guidance.